Intercultural service encounters: Cross-cultural interactions and service quality - Sharma, Piyush (2018)
This book investigates intercultural service encounters (ICSEs) in light of the rapidly globalizing world economy, examining the extant literature on the topic and identifying areas which require further exploration. With a focus on intercultural communication and competence, the author analyses diverse conceptual frameworks, providing theoretical models and practical initiatives for those working within the services marketing industry. An excellent resource for anyone interested in how culture shapes customer and employee expectations and perceptions, this book addresses the potential implications and limitations of future models.